Reducing Pb accumulation in roots of sweet potato under low lead-contaminated soil by Azotobacter inoculation - Reginawanti Hindersah; Vera Oktavia Subarja; Pujawati Suryatmana; Rija Sudirja; Agung Karuniawan; Yusup Hidayat (Brawijaya University, 2023)
Agricultural soil is possibly threatened by lead (Pb) contamination due to the intensive use of fertilizers. The rhizobacteria were recommended for the bioremediation of soils contaminated by low concentrations of Pb. The experiment was conducted to observe the Azotobacter's ability to proliferate in Pb-contaminated broth and to decrease the Pb availability in soil, Pb uptake by sweet potato roots, and sweet potato growth. The resistance test was performed by growing five Azotobacter isolates in N-free broth with various Pb levels. A pot experiment was conducted in a factorial randomized block design to test three levels of Pb in soil and two Azotobacter isolates. The results showed that Azotobacter Azv4 and A. choroococcum were resistant to 100 mg L-1 Pb in N-free broth. In the pot experiment, Azotobacter Azv4 Inoculation caused less Pb in soil and roots of sweet potatoes grown in Pb-contaminated soil than A. choroococcum. Either Azotobacter or Pb soil did not influence vine length. However, Azv4 was more prominent in increasing branch number, root volume and length; higher Pb in soil reduced branch number but did not affect root parameters. Azotobacter Azv4 increased more shoot and root dry weight compared to A. choroococcum, but both isolates did not change the shoot-to-root ratio (S/R). The Pb contamination only reduced root dry weight and reduced the S/R. This research considered utilizing rhizobacteria Azotobacter for reducing Pb levels in soil and roots; and increasing sweet potato biomass.